Relative validity of a self‑dietary assessment nutrition application compared with a 3‑day food record in non‑dialysis chronic kidney disease: A prospective study - Arayangkoon, Chantisa; Siriyong, Patchanon (Narra J, 2026)
Accurate and repeated dietary assessment is essential for nutritional management in chronic kidney disease (CKD); however, conventional methods, such as the 3-day food record, are burdensome for routine clinical use. Digital self-administered dietary assessment tools may offer a practical alternative; however, validation data in non-dialysis CKD, particularly among Asian populations, remain limited. This study aimed to evaluate the relative validity of a locally adapted digital self-dietary assessment application (Nutrirodcal) compared with a 3-day food record in patients with non-dialysis CKD. This prospective single-center study enrolled adults with non-dialysis CKD stages 3–5. Participants completed both a 3-day food record (reference method) and Nutrirodcal every 4 weeks for 12 weeks. Correlations between the two methods were assessed for energy, macronutrients, minerals, and fluid intake. Changes in nutritional status, biochemical parameters, and body composition were assessed as secondary outcomes. Twenty participants completed the study. At week 12, Nutrirodcal showed moderate-to-strong correlations with the 3-day food record for energy, protein, sodium, potassium, calcium, and phosphorus intake (Spearman r=0.50–0.65; all p<0.05). Correlations for fluid intake were weak at weeks 4 and 12 but reached a moderate and statistically significant level at week 8 (r=0.55, p=0.012). Over the study period, body mass index decreased significantly without deterioration in serum albumin or kidney function, while other biochemical and body composition parameters remained stable. Nutrirodcal demonstrated acceptable relative validity for assessing key nutrient intakes relevant to CKD management compared with a 3-day food record. This Thai-adapted digital tool may support repeated dietary monitoring and patient engagement in non-dialysis CKD care, although dietitian oversight remains essential, particularly for fluid intake assessment.